Dengue fever in the Indian subcontinent: an overview - Ummar Raheel; Muhammad Faheem; Mohammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Journal of Infection in Developing Countries)
The Indian Subcontinent has emerged as a scene of many mosquito-borne infectious diseases, including malaria and dengue fever. After the 1990s, the rate of malaria declined owing largely to preventive measures, but at the same time dengue fever (DF) and dengue hemorrhagic fever (DHF) were increasing in the region. Outbreaks were recorded in all countries of the Indian Subcontinent with India, Pakistan, Bangladesh and Sri Lanka on the forefront and suffering from the largest number of cases and deaths. We discuss annual cases of DF/DHF in these four countries and possible factors involved in DF outbreaks. We also discuss prevalent serotypes in this region where data suggest the emergence of DEN2 and DEN3 as the most dominant and lethal serotypes. Climate is an important factor influencing DF outbreaks, and rainfall, temperature and humidity play a pivotal role in DF outbreaks. Finally the economic impact of DF/DHF cases is discussed showing that direct and indirect economic loss due to DF/DHF reaches millions of USD each year.